Study guides

Q: What is 5a- 2a?

Write your answer...

Submit

Related questions

2a + 3a = 5a

2a - 5a = -3a

It is: 2a+5a = 7a when simplified

2a-8+4=45-5a 2a-4=45-5a 2a-4+4=45+4-5a 2a+5a=49-5a+5a 7a=49 / by 7 = A=7

assuming 5a-a-2a-18=0 2a-18=0 2a=18 and thus a=9

Add them together: 2a+5a = 7a

9a +8 -2a -3 -5a = 2a +5

2a+5a+9a = 16a

2a + 5a + 3a = 10a

2a + 10 + 5a - 2 = (2a + 5a) + (10 - 2) = 7a + 8

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

2a + 11a - 5a = 8a

5a + 3 + (2a - 2) + a= 5a + 3 + 2a - 2 + a= 8a + 1

-7a+2a+9 is also -5a+9. -5a+9=24. -5a=15. a=-3.

If you mean: (2a+9)(5a-6) then it is 10a^2+33a-54

The value of a in the equation 5a plus 2a = 6-6a is a=6/11.

7

(5a+8) - (2a+4) =3a +4 To do this, simply subtract like terms. 5a-2a=3a and 8-4=4

5a-20+2a = 6a-11 5a+2a-6a = 20-11 1a = 9 a = 9

3a + 2a = 5a

If: 2a+13 = 5a+1 Then: a = 4

5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.

2a-5=-3a5a-5=05a=5a=0

i dont understand what you mean by symbolic but ill just do an example 2a + 3 = 4 - 5a first collect like terms 2a +3 -3 = 4 -3 -5a 2a = 4-3 - 5a 2a + 5a = 1 - 5a + 5a 2a + 5a = 1 7a = 1 divide both sides by the coefficient of the unknwown(i.e. the number in front of the letter) 7a/7 = 1/7 a = 1/7

2a + 3b

People also asked